Municipal Support-Options for Energy Sufficiency by the Formation of Framework Conditions. A Mixed Methods Analysis of the Electricity Tariff KlimaFix by Stadtwerke Heidelberg. - Leuser, Leon (My University, 2014)
In this study the question of how and to what extent services provided by municipal institutions can induce changes in consumption patterns of individuals to decrease energy demand through the provision of options and changes of framework conditions shall be addressed. The motivation is to explore policy options supporting energy sufficient practices, as there is increasing evidence that the technological strategies of efficiency and consistency are insufficient to substantially decrease energy demand of households. Therefore, innovative policy approaches for a sufficiency strategy shall be explored in order to supplement the former two for a comprehensive sustainability transition.
Keywords: Energie; Energieeinsparung; Energiebedarf; Energieverbrauch; Energiepolitik; Gemeindeunternehmen; Suffizienz; Analyse; Stadtwerke